2021
DOI: 10.31004/basicedu.v6i1.1897
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Iklim dan Budaya Sekolah di Masa New Normal terhadap Penguatan Pendidikan Karakter Berbasis Budaya Lokal Po-5 Sejak Dini

Abstract: Karakter budaya lokal Po-5 merupakan warisan nilai budaya Kesultanan Buton yang sangat penting untuk diimplementasikan dalam kehidupan sehari-hari yang sangat berkesesuaian dengan nilai-nilai Pancasila dan agama dalam membentuk karakter unggul bermartabat di masyarakat. Penelitian ini bertujuan untuk menganalisis peran iklim dan budaya sekolah dalam memberikan penguatan karakter berbasis budaya lokal sejak dini. Metode penelitian ini termasuk penelitian deskriptif dengan menggunakan instrument penelitian berup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
2
0
4
Order By: Relevance
“…Our previous research found several strategies for strengthening character education that can be strengthened through the school climate and culture with self-development programs, curricular, extracurricular and cocurricular activities listed in the vision and mission of the school curriculum so that these activities are more directed, consistent, structured, and well planned so that they cannot achieve the expected character values (Aswat, et al: 2022). In line with the other study found that "intellectual character education," which emphasizes the development of intellectual virtues like curiosity, openmindedness, and intellectual courage, is an underexplored but especially promising approach in this context (Baehr, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research found several strategies for strengthening character education that can be strengthened through the school climate and culture with self-development programs, curricular, extracurricular and cocurricular activities listed in the vision and mission of the school curriculum so that these activities are more directed, consistent, structured, and well planned so that they cannot achieve the expected character values (Aswat, et al: 2022). In line with the other study found that "intellectual character education," which emphasizes the development of intellectual virtues like curiosity, openmindedness, and intellectual courage, is an underexplored but especially promising approach in this context (Baehr, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the research by Solihah et al, (2022) stated that character strengthening was successfully carried out by management making clear stages, namely planning, organizing, implementing, and supervising. Conversely, strengthening unstructured and planned characters in the curriculum causes the expected character values to not be achieved (Aswat, et al, 2022).…”
Section: Strengthening Student Character Through Local Wisdommentioning
confidence: 99%
“…Inovasi guru dalam pembelajaran salah satunya adalah dengan bentuk penerapan budaya lokal dalam proses pembelajaran. Aswat et al, (2022) dalam penelitiannya menyatakan bahwa pembelajaran budaya lokal yang dimiliki oleh masyarakat setempat sangat penting untuk diterapkan. Hal ini mengingat bahwa dengan pembelajaran berbasis budaya lokal siswa dapat mengenal nilai-nilai karakter masyarakat setempat yang perlu ditanam.…”
Section: Pendahuluanunclassified